Severe maternal morbidity and breastfeeding outcomes in the early post‐natal period: a prospective cohort study from one English maternity unit. Issue 4 (26th February 2015) - Furuta, Marie; Sandall, Jane; Cooper, Derek; Bick, Debra
Abstract: Previous research has identified potential issues of establishing and maintaining breastfeeding among women who experience severe maternal morbidity associated with pregnancy and birth, but evidence in the UK maternity population was scarce. We explored the association between severe maternal morbidity and breastfeeding outcomes (uptake and prevalence of partial and exclusive breastfeeding) at 6 to 8 weeks post‐partum in a UK sample. Data on breastfeeding outcomes were obtained from a large cohort study of women who gave birth in one maternity unit in England to assess the impact of women's experiences of severe maternal morbidity (defined as major obstetric haemorrhage, severe hypertensive disorder or high dependency unit/intensive care unit admission) on their post‐natal health and other important outcomes including infant feeding. Results indicated that among women who responded ( n  = 1824, response rate = 53%), there were no statistically significant differences in breastfeeding outcomes between women who did or did not experience severe morbidity, except for women with severe hypertensive disorder who were less likely to breastfeed either partially or exclusively at 6 to 8 weeks post‐partum. Rather, breastfeeding outcomes were related to multi‐dimensional factors including sociodemographic (age, ethnicity, living arrangement), other pregnancy outcomes (neonatal intensive care unit admission, mode of birth, women's perceived control during birth) and post‐natal psychological factors (depressive symptoms). Women who experience severe maternal morbidity can be reassured that establishing successful breastfeeding can be achieved. More studies are required to understand what support is best for women who have complex health/social needs to establish breastfeeding.